SCHOEMAN, Stephanus Andries Ignatius Inventory of documents - SCHOEMAN, Stephanus Andries Ignatius (ARCA, 2018)
Private papers of S.A.I. Schoeman, Clerk S.A. Railways.
COVERAGE 1918-1935, 1976; 4 Files; 0.11 metre
Keywords: SCHOEMAN, Stephanus Andries Ignatius; Inventories; Politicians; National Party